Larangan Menjual Barang yang Sudah Dijual: (Kajian Tematis Hadis Riwayat Bukhari No. 1995, bab al-Buyu’) - Sobari, Alwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
Prophet Muhammad in some of his hadiths explained about the prohibition of goods already sold. And at least, there are some trading practices that prohibited by him in his hadiths, namely the prohibition of buying goods that have been purchased, the prohibition of selling goods that have been sold and bid on the offer of others. Some of the above – mentioned restriction apply if they satisfy some elements. For example, there is ni prior agreement between the parties that are transacting. It is prohibited because there is an element of hurting and tyrannizing towards others.